2007
DOI: 10.1111/j.1365-2672.2007.03317.x
|View full text |Cite
|
Sign up to set email alerts
|

Biohydrogenation of linoleic acid by rumen fungi compared with rumen bacteria

Abstract: Aims:  To investigate biohydrogenation of linoleic acid by rumen fungi compared with rumen bacteria, and to identify the fungus with the fastest biohydrogenation rate. Methods and Results:  Biohydrogenation of linoleic acid by mixed rumen fungi and mixed rumen bacteria were compared in vitro. With mixed rumen bacteria, all biohydrogenation reactions were finished within 100 min of incubation and the end product of biohydrogenation was stearic acid. With mixed rumen fungi, biohydrogenation proceeded more slowly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 32 publications
1
34
1
2
Order By: Relevance
“…Fungi (table 2) represent a small proportion, approximately 8%, of the biomass in the ruminal ecosystem (Jenkins et al 2008), but they do have a role in the digestion of food consumed by the ruminant (Nam and Garnsworthy 2007). Some fungi are microaerotolerants and are attached to feed particles through a system of rhizoids (Denman et al 2008).…”
Section: Ruminal Fungimentioning
confidence: 99%
“…Fungi (table 2) represent a small proportion, approximately 8%, of the biomass in the ruminal ecosystem (Jenkins et al 2008), but they do have a role in the digestion of food consumed by the ruminant (Nam and Garnsworthy 2007). Some fungi are microaerotolerants and are attached to feed particles through a system of rhizoids (Denman et al 2008).…”
Section: Ruminal Fungimentioning
confidence: 99%
“…Characterizing the formation of intermediates and production of end products arising from the biohydrogenation of lipids in the rumen is central to attempts to enhance the nutritional attributes of ruminant milk fat. Biohydrogenation has been studied for many years, most recently in attempts to identify species that form isomers of conjugated linoleic acid (CLA) as transient intermediates during the metabolism of linoleic acid (cis-9,cis-12-18 : 2) to 18 : 0 (Kim et al, 2002;Paillard et al, 2007;Wallace et al, 2006;Nam & Garnsworthy, 2007) and the mechanisms responsible for CLA synthesis . Isomers of CLA also serve as a substrate for reduction to 18 : 1 intermediates and 18 : 0 (Kepler et al, 1966;Harfoot & Hazlewood, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an in vitro study demonstrated that rumen fungi have the capacity to biohydrogenate LA, with Orpinomyces fungus being the most active. RBH is slower in fungi than in bacteria and has trans-11-18:1 as the end product (Nam and Garnsworthy, 2007).…”
Section: Microorganisms Involved In Rumen Biohydrogenationmentioning
confidence: 99%